Effect of heat flow via glazing on the productivity of a solar still - Khechekhouche, Abderrahmane; Driss, Zied; Durakovic, Benjamin (جامعة الوادي - university of el oued, 2019)
In many parts of the world, particularly in the Greater Maghreb, desalination of water by solar energy is practiced with incredible abundance. Drinking water shortage has become a major problem. Improving the efficiency of solar distillers in several laboratories around the world is still one of the major concerns of research topics. In this work we want to show that the heat flow through the glazing can also be considered as an index on the productivity of pure water from a conventional solar still.
Article Article
Keywords: Solar energy; solar distiller; distilled water; drinking water.